SIKAP RUSIA TERHADAP PROTOKOL PERJANJIAN SEANWFZ (SOUTHEAST ASIA NUCLEAR WEAPONS FREE ZONE) - Hamid, Luqman; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This study describes Russia‟s decision in Treaty of South-East Asia Nuclear Weapons Free zone (SEANWFZ) or as know as Bankok Treaty, this treaty is one of treaty Nuclear Weapons Free Zone (NWFZ) that already exist in the few regional in the world. These day there are five treaties, Tlateloco Treaty (America Latin and carribia), Rorotonga Treaty (South Pacific), Bangkok Treaty (SouthEast Asia), Pelindaba Treaty (Africa), and NWFZ in Central Asia (Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan and Uzbekistan). In general this treaty has role about nuclear weapons, such as; prohibit development, testing, manufacture, posssession and everything that have relation with nuclear weapons in the designed teritory,and prohibit use or threat of use nuclear againts another nations. Same like the other treaty of NWFZ, to make SEANWFZ treaty can be implemented it needs admitation and ratification from 5 security council of UN or Nuclear Weapons States (NWS). But in the development of this treaty Russia take a stand to refused this treaty.The theory that applied in this research is neo-realism as paradigm where the international system give influence to the national or states decision or the policy that they were made. Level analysis in this research is System Level Analysis, cause it can explained and give anlaysis in comprehensive scope for every single interaction of actors in one system where they interact.researcher also use theory from Viotti and Kauppi about policy decision is influence by interest, opportunities, threats, and capabilitiesThe study found that the Russia‟s reasons take a stand to refuse ratification this treaty are because SEANWFZ; is not reputed or not considered ready for NWFZ concept, the designed teritory that they were made is to wide because include ZEE and also Russia has interest in South China Sea about spreads the Russia‟s economic, plus more ASEAN and China still have teritory conflict in South China Sea, and the ambiguity of ASEAN to support world peace from nuclear weapons.Keywords : ASEAN, nuclear weapons, NWFZ, SEANWFZ Treaty, Russi